Hambatan Komunikasi Antar Budaya Pendatang Jawa Terhadap Masyarakat Suku Minang di Nagari Sungai Pua Kabupaten Agam - Adilla Warni; Penmardianto Penmardianto (Student Research Journal, 2023)
This study focuses on intercultural communication barriers of Javanese immigrants to the Minang Tribe Community in Nagari Sungai Pua, Agam Regency. This research is motivatetd by the problem of the obstacles felt by Javanese migrants while living in Nagari Sungai Pua. Intercultural communication barriers for Javanese immigrants in Nagari Sungai Pua, where language and culture are the most important obstacles felt by Javanese migrants. Communications barrieris often arise when there are differencess in background. culturalt background. When communicating, Javanese immigrants find it difficult to understand the language used, so that Javanese immigrants are less intense in socializing with the local community, as well as misunderstandings between Minang people and Javanese immigrants. Misunderstanding of cultural understanding can certainly hinder effective communications. The purpose of this studys was to findd out how the barriers to intercultural communicatiotn of Javaenese immigrants towards the Minang Tribe Society in Nagari Sungai Pua, Agam Regenchy. The tyipe of research used is field researjch swith a descriptive qualitativie approach. The research location isn in Nagari Sungai Pua, Agam Regency. This study used a purposive sampling technique. Sources of data in this study were obtained from observations, interviews and documentation. Meanwhile, to analyze the data the authors use data regduction, data presentations, and conclusiconts. The results of this study indicate that the reseanrcher fonund nine interculftural communication barriers feilt by Javanese immigrants towards the Minang Tribe in Nagari Sungai Pua, Agam Regency, including language, cultural, physical, emotional, non-verbal, competition, perception,